Research on Energy-Related CO2 Emissions Characteristics, Decoupling Relationship and LMDI Factor Decomposition in Qinghai - Huang, Can; Zhou, Yin-Jun; Cheng, Jin-Hua (Frontiers in Energy Research, 2021)
Based on the statistical data from 1997 to 2017, using the IPCC carbon accounting method, Tapio decoupling model and Logarithmic Mean Divisia Index (LMDI), the temporal evolution characteristics of Qinghai’s energy-related carbon emissions, the decoupling relationship and its driving factors are analyzed. The results show that: (1) The carbon emissions of Qinghai showed a trend of first slowly increasing, then rapidly increasing, and finally fluctuating and decreasing. It increased from 3.85 million tons in 1997 to 14.33 million tons in 2017, with an average annual growth rate of 6.79 %. The carbon emission intensity showed a steady downward trend, from 189.82 tons/ million CNY in 1997 to 54.6 tons/ million CNY in 2017, with an average annual growth rate of -6.04%. (2) The relationship between carbon emissions and economic growth is represented by four types: weak decoupling, strong decoupling, expansion negative decoupling, and expansion coupling. Among them, a strong decoupling was achieved only in the five periods of 1997-1998, 1999-2000, 2001-2002, 2013- 2015 and 2016-2017. (3) The structural effect of energy consumption is the most important factor in restraining carbon emissions, followed by the energy intensity effect, while economic growth and population size are important factors that promote the increase in carbon emissions. Therefore, Qinghai should continuously optimize its energy structure, improve energy utilization efficiency, thus to achieve economic green and high-quality development.